Feasibility Study on the Relocation of the Mrican Ponorogo Landfill in 2024 - Aliyadi (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The problem of waste management in Ponorogo Regency is increasingly complex along with the growth of the population and the increase in the volume of waste. One of the waste management locations that is facing problems is the Mrican Landfill, which has been operating since 1995 and is now experiencing excess capacity. This study aims to evaluate the feasibility of relocating the Mrican Landfill to a new location that is wider and in accordance with technical, social, and environmental criteria. This feasibility study uses a multicriteria analysis approach involving Simple Additive Weighting (SAW) methods and SWOT analysis, as well as GIS techniques for site suitability evaluation. The results of the study show that the new 9.38-hectare site can accommodate waste for 28 years with a capacity of around 2,900,000 m³ or 750,000 tons. This relocation is feasible from various aspects, including environmental, social, economic, and technical. The selection of a new location meets the criteria of SNI No. 03-3241-1994, with considerations such as safe distance from settlements, topographic conditions, accessibility, and minimal risk of pollution. This research also recommends improving supporting infrastructure, an efficient waste management system, and socialization programs to the community. The relocation of this landfill is expected to improve the quality of waste management and support environmental sustainability in Ponorogo Regency.